Characterization of polyphenoloxidase (PPO) extracted from "Jonagored" apple - Rocha, A.M.C.N. (2011)
Polyphenoloxidase (PPO) was extracted from apple (cv. Jonagored) with addition of 2% PVP and 0.25% Triton X100 to the extraction buffer containing phenolic adsorbents. Experiments were performed to evaluate the affinity and specificity towards several substrates. ‘Jonagored’ apple PPO was found to have higher specificity (lower Km) towards L-dopa, 4-methylcatechol and (+) catechin than other phenols tested, but the highest activity level was obtained with p-cresol. The ratio Vmax/Km indicates that p-cresol followed by L-dopa and 4-methylcatechol are the best substrates for ‘Jonagored’ apple PPO. The enzyme activity showed two pH optima, at 5.0 and 7.5, at room temperature, with the main peak at pH 7.5 and the secondary one at pH 5.0 when catechol was the substrate.